Nanoanalysis of the leaching process simulation of Pb in agricultural soil. (1st August 2022) - Liu, Shuyu; Min, Xin; Xiang, Minghui; Wang, Jiangli; Tang, Lei; Liu, Li
Abstract: Using the Spectral characteristics of gold nanorods to investigate heavy metals Pb in agricultural soils. Studied included: (1) The effects of humic acid on Pb transformation and its formation changing were explored. The laboratory model was established to simulate Pb leaching process in the soil and investigated the change of total Pb content at different layers. (2) The migration and transformation of different forms Pb were studied by the nano system. The effect of humic acid and pH were analyzed based on the nano-analysis method. (3) The relationship between various forms Pb irons were analyzed. (4) The data showed that ion exchange state and iron-manganese oxidation state Pb were more likely to enriched at 0 cm depth, and organic bound state was more likely to enriched at 10 cm depth. Humic acid increased the solidify ability of different forms of Pb in agricultural soil, and the analysis system was efficient to supply the exactly transition process. Graphical abstract: Image 1 Highlights: The concentration of hydrogen ions decreased during the leaching process. Cation exchange led to carbonate-bound state Pb content decreasing. The oxidation state and manganese state Pb at 0 cm was higher than 10 cm. Most of Pb was easy enriched on the soil surface.